2012
DOI: 10.1177/0960327112446842
|View full text |Cite
|
Sign up to set email alerts
|

Increased oxidative stress is associated with the development of organophosphate-induced delayed neuropathy

Abstract: Organophosphate-induced delayed neuropathy (OPIDN) is a progressive neuropathic disorder that manifests in days to weeks following exposure to an acute dose of organophosphates. The precise mechanism involved in the development of OPIDN is not clear as it develops after many days of the cessation of cholinergic crisis. The present study has been designed to understand the role of oxidative stress in the development of OPIDN, wherein neuropathy was developed by the administration of acute dose of monocrotophos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…So OPIDN in hens can not be completely simulated in human. OPIDN in mammals has been also successfully established in rats [41,42]. So in our further research, we will observe the effect of Apelin-13 on the OPIDN in rats.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…So OPIDN in hens can not be completely simulated in human. OPIDN in mammals has been also successfully established in rats [41,42]. So in our further research, we will observe the effect of Apelin-13 on the OPIDN in rats.…”
Section: Discussionmentioning
confidence: 88%
“…This study provides novel evidence that application of Apelin-13 for OPIDN and Apelin-13 may be a potential drug in clinical applications for OPIDN. OPIDN is characterized by ataxia that progresses to paralysis concurrent with a central-peripheral distal axonopathy after a delay period of 1-3 weeks following exposure to OP [34]. TOCP is a well-studied organophosphate which causes the OPIDN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brain of aged patients showed a reduced catalase functionality [55], similarly catalase activity was affected in a rat model of Parkinson’s disease [56]. Catalase impairment was also described in neuropathic conditions since decreased catalase efficiency was described in sciatic nerve of rats affected by diabetic neuropathy [57] as well as in brain regions of animals with delayed neuropathy induced by organophosphate [58]. On the other hand, the oxidative unbalance of these painful conditions has never been associated with peroxisome alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the inhibition of acetylcholine esterase, DZN causes remarkable atropine-insensitive hypotension in rats when administered intravenously in lethal doses and exerts vasorelaxant actions in endothelium-denuded rat aorta (Kojima et al, 1993). Moreover animal studies showed that DZN increases oxygen free radicals (Shadnia et al, 2005) and oxygen free radicals play a role in OPs toxicity including delayed neuropathy (Masoud & Sandhir, 2012;Ogutcu et al, 2006), a progressive neuropathic disorder that develops after many days of the cessation of cholinergic crisis. Furthermore some studies showed that cardiovascular toxicity induced by OPs could be related to the oxidative stress (Kumar & Jugdutt, 2003), and antioxidants can suppress toxicity (Guney et al, 2007;Kumar & Jugdutt, 2003).…”
Section: Introductionmentioning
confidence: 99%